Pelatihan Pembuatan Sirup Jeruk Kunci Ibu-Ibu Rumah Kelurahan Pal Lima Kota Pontianak - Athiah Masykuroh; Nadia Nia Nurulita; Nita Abna (Empowerment: Jurnal Pengabdian Masyarakat, 2022)
The COVID-19 pandemic causes everyone have to taking care of theirself and families starts from clean and healthy habit by consume meals and drinks which is rich an antioxidants containing for body immune system maintaining. The syrup was one of consuming drinks which could accommodate that purpose and be economical chance for the people. The step of this coaching was consist of giving material session, make practice for the syrup and then evaluate the knowledge of the respondents by pre-test and post-test checking to measure succeed level of the coaching. The result,after coaching the knowledge of the respondents about Citrus microcarpa Bunge and it’s potency for syrup making was increased.